Kajian Literatur (Systematic Literature Review): Kendala Penerapan Sistem Pemerintahan Berbasis Elektronik (SPBE) - Arief, Assaf; Abbas, Muhammad Yunus (PROtek : Jurnal Ilmiah Teknik Elektro, 2021)
Electronic-based Governance System (SPBE) or known as e-government is an effort to utilize information and communication technology to support government systems and improve the effectiveness and efficiency of government institutions' performance. The implementation of e-government is expected to improve the quality of public services. E-government in thecountry will usually face many obstacles that can be thwarted in its application. Previous research has discussed more about the constraints of e-government implementation in developing countries. This study aims to identify the obstacles faced in the application of SPBE/e-government in developing and developedcountries. This research uses systematic literature review method by Kitchenham. The literature used in this study was taken from several digital Library, namely ACM Digital Library, IEEE Xplore, Science Direct, and Scopus. The results of the study found thatconstraints in its application in developing and developed countries can be categorized into seven constraints / aspects, namely IT Infrastructure, Human Resources, Policy / Legislation, Politics, Economy, Geography and Culture. These constraints can be a reference for the government to make improvements in the implementation of SPBE so that the quality of services can be better